The nature of engineering and science knowledge in curriculum: a case study in thermodynamics - Smit, Reneé (Department of Chemical Engineering, 2017)
Abstract The study explores the nature of disciplinary knowledge differences and similarities between the sciences and the engineering sciences as these appear in curriculum texts. The work is presented as a case study of curriculum knowledge in thermodynamics, and the epistemic properties are investigated in four sub-cases in mechanical engineering, chemical engineering, physics and chemistry. Data was collected from prescribed undergraduate textbooks in the four disciplinary fields. The work is theoretically informed by two fields of scholarly work: the sociology of educational knowledge (in particular the work of Basil Bernstein) and the applied philosophies of science and engineering science, in order to develop a theoretical framework for analysis of the data. The framework allows the study to move beyond the typical binary classification of the sciences as 'hard-pure' and engineering sciences as 'hard-applied' disciplines. Starting from broad teleological considerations, the philosophical concepts of specialisation, idealisation and normativity are explored and developed into modalities and modal continua of variance to allow investigation of the epistemic differences and similarities in the recontextualised disciplinary knowledge from these contiguous conceptual fields. The empirical study identifies important differences in thermodynamics curriculum knowledge in terms of specialisation, normativity and idealisation across the broad disciplinary fields, rendering more complex Bernstein's notions of singulars and regions. The epistemic modalities and modes provide a way to conceive in more detail how the professional engineering science knowledge is orientated towards its field of practice. Curriculum knowledge in the engineering sciences is shown to be remarkably different from the knowledge in the sciences: both mechanical and chemical engineering knowledge emphasise particulars, rather than universals, have stronger normative aspects, and employ a limited form of idealisation in their commitment to physical realisability. By contrast, knowledge in the sciences is more universal, normativity is incidental, and idealisation is used expansively. In addition, the research findings suggest a negative correlation between idealisation and normativity as epistemic modalities: a commitment to normative concerns in the engineering sciences constrains the extent to which knowledge idealisation is pursued, compared to what is observed in the bodies of science curriculum knowledge. Furthermore, over and above differences in curriculum knowledge between the broad fields of science and engineering science, discernible variation exists between the engineering sciences investigated, raising cautions against a monolithic view of curricular epistemic properties across broad disciplinary areas.